The Kará’an Songs of Romblon: A Proposed Framework on Regional Folkloric Research - Perlas, Sherwin (Romblon State University Research Journal, 2014)
Philippine regional oral literature scholarship is currently navigating against the current from the preiphery to the center. Romblon’s oral tradition is likewise sailing across the tibulent sea. While a number of works had been anthologized and had undergone scrutiny, apparently not much exploration has been given to the proper collection, translation, and subsequent analysis. This paper proposes a paradigm in collective Romblon’s oral tradition, in particular and any regional oral tradition, in general. The collection, documentation, authetication, trasnlation and analysis used the suggested hollistic apporach. In this study, the methods and apporaches were discussed, the steps were outlined and the scholarly implications were identified. The main research question is a descriptive-analytic documentaiton of the tradition: What are the surviving kará’an oral literatures of Romblon based on primary secondary sources? The process starts from collecting the tradition secondary sources: the province’s historical data found in microfilm, internet posts, email correspondences, and personal collections tracked and documented in the field. The text’s provenance, singer, context of singing, audience reaction, historical, cultural, and geographical relevance - the "metadata"and filed notes - were likewise recorded with the researcher interpreting data from the informants’perspectives. The focus of investigation is proper documentation that ensures authenticity of materials that could then be subjected to trasnlation, and literary analysis.